Concurrent and prospective associations between bullying victimization and substance use among Australian adolescents. (1st September 2015) - Kelly, Erin V.; Newton, Nicola C.; Stapinski, Lexine A.; Slade, Tim; Barrett, Emma L.; Conrod, Patricia J.; Teesson, Maree
Highlights: This study examined concurrent and longitudinal associations between bullying victimization and substance use among Australian adolescents. Bully-victim status at age 13 was associated with risky drinking and cannabis use at age 15. Associations between bullying victimization and substance use were evident for bully-victims but not passive victims. Abstract: Background: Adolescence is a vulnerable time for both substance use and bullying involvement; however, there is limited research on substance use among adolescent victims of bullying. This study aimed to examine concurrent and prospective associations between bullying and substance use, differentiating between passive-victims, bully-victims and 'pure' bullies. Method: Associations between bullying involvement and substance use at baseline and 24 months post-baseline were examined in a cohort of adolescents in Australia. Bullying victims were divided into passive-victims (those who get bullied and do not bully others) and bully-victims (those who both get bullied and bully others). Perpetrators of bullying were divided into 'pure' bullies (those who bully others but do not get bullied), and bully-victims (as above). Outcomes examined were past six month use of alcohol (any drinking; risky drinking), tobacco, and cannabis. Results: While there was no evidence of an association between bullying victimization and/or perpetration and substance use at baseline, there was evidence of an association between bullying and substance use 24 months post-baseline. Specifically, there was evidence of increased odds of risky drinking and cannabis use for the bully-victim group. Conclusions: Bully-victim status at age 13 was associated with substance use at age 15, controlling for concurrent bullying involvement at age 15. Bully-victims are a particularly high-risk group that could benefit from targeted substance use preventive interventions. Reducing bullying is of great importance in reducing substance use and other harms among adolescents.